INVESTIGATION INTO THE IMPLEMENTATION METHODS ADOPTED BY STATE AGENCIES FOR ADULT LITERACY PROGRAMMES TO FOSTER SUSTAINABLE MASS LITERACY IN SOUTH‑EAST NIGERIA (International Nexus Multidisciplinary Research Journal, 2026)
Adult literacy remains a pressing challenge in South East Nigeria, where state agencies have introduced programmes to foster sustainable mass literacy. Despite these initiatives, literacy outcomes remain uneven, necessitating an investigation into the instructional methods employed. A survey design was adopted, involving 250 teachers across rural and urban schools. Respondents provided data on the use of conventional methods, Each-One-Teach-One (EOTO), literacy clubs, literacy by radio, literacy campaigns, and stakeholder meetings. Percentages of agreement and disagreement were analyzed to determine the prevalence and effectiveness of each method. Findings revealed that conventional methods such as lectures, discussions, and drama were the most widely adopted (26.6% rural, 35.2% urban). Stakeholder meetings also recorded notable usage (20.4% rural, 30.8% urban). Conversely, participatory and innovative approaches were underutilized: EOTO methods (12.2% rural, 19.6% urban), literacy clubs (13.2% rural, 26.4% urban), literacy by radio (15.2% rural, 24.0% urban), and literacy campaigns (17.6% rural, 23.2% urban). High levels of disagreement across these categories further underscored their limited implementation. The study concludes that adult literacy programmes in South East Nigeria rely predominantly on conventional instructional strategies and stakeholder engagement, while innovative, learner-centered methods remain marginal. To achieve sustainable mass literacy, state agencies must diversify their approaches by integrating participatory, community-driven, and technology-based strategies that enhance adult learning outcomes and long-term literacy development.